The Rainbow of Life: A collective narrative practice with young LGBTQIA+ people with a health condition - James McParland; Jaymie Huckridge (International Journal of Narrative Therapy and Community Work, 2024)
This article describes the use of narrative practices for LGBTQIA+ young people with a health condition. It presents a collective narrative practice: the Rainbow of Life. This adapts the Tree of Life metaphor to invite rich story development opportunities when working with LGBTQIA+ people. It involves exploring their commitments, special moments and those who stand alongside them in solidarity, and creatively mapping these on to a rainbow image. The authors outline Rainbow of Life events they have organised, including collective practices in which young people shared their wisdom for responding to oppressive storm clouds that darken the sky and dim their rainbow’s shine, as well as witnessing and honouring each other’s rainbows.